Social Support Improves the Quality of Life Among Institutionalized Older People in The Social Protection Center, Banten Province, Indonesia - Delly Afra Syukrowardi; Deni Suwardiman; Bambang Kuntarto (Ruang Ide, 2022)
Background: Optimal quality of life is the hope of all older people. In the life span of older people, they experience a period where they are faced with a difficult situation that results in stress or even a traumatic bad experience. Several supporting factors are needed for older people to achieve optimal quality of life. Aims: This study was aimed to determine the predictor factors of the quality of life of institutionalized older people. Methods: This study used a correlation analysis design and a cross-sectional approach. Samples in this study were 50 older people at the Banten Social Protection Center. Data was collected by using questionnaires consisting of WHO Quality of Life, Barthel Index, HAM-A, and social support. Results: This study found that there was a strong relationship between quality of life with stress levels (p <0.01), level of dependence (p <0.05), and social support (p <0.01). The result of further analysis using multiple regression found that social support (Beta = 0.345, p <0.05) was found to be a predictor of quality of life for institutionalized older people. Conclusion: Quality of life of older people can be achieved to be optimal by increasing the social support surrounding. Thus, this study suggests the Banten Social Protection Center can facilitate to seek social support from both external and internal. Keywords: Quality of life, institutionalized older people, social protection center, Banten.